Gyrosigma arcuatum Sterrenburg ... - Al-Handal, Adil Y.; Torstensson, Anders; Wulff, Angela (Zenodo, 2022)
Gyrosigma arcuatum (Donkin) Sterrenburg (Figure 79) Literature: (Jahn et al. 2005, p. 306, fig. 8). Description: Length 85–90 µm, width 13–14 µm, striae not resolved under LM. Remarks: This species has rarely been described in recent literature but is mentioned only in diatom checklists from Europe and North America (e.g., Hendey 1974; Mather et al. 2010) and is mostly referred to as G. fasciola var. arcuata (Donkin) Cleve. The species can be easily distinguished from G. fasciola by its shorter and strongly arcuate valve poles. Jahn et al. (2005) typified this species and separated it from G. fasciola. Ecology and distribution: It is difficult to trace the distribution of this species as in many records it might have been confused with G. fasciola. It does not seem to have been reported from Antarctica even in its varietal rank but was observed in the sub-Arctic (Cardinal et al. 1986 as var. arcuata). The species has not been observed in previous samples from Potter Cove. Rare in the present material. ... : Published as part of Al-Handal, Adil Y., Torstensson, Anders & Wulff, Angela, 2022, Revisiting Potter Cove, King George Island, Antarctica, 12 years later: new observations of marine benthic diatoms, pp. 81-103 in Botanica Marina (Warsaw, Poland) (Warsaw, Poland) 65 (2) on pages 93-94, DOI: 10.1515/bot-2021-0066, http://zenodo.org/record/11000147 ...